Identifying pathways to early‐onset metabolic dysfunction, insulin resistance and inflammation in young adult inpatients with emerging affective and major mood disorders. Issue 10 (1st December 2021) - Tickell, Ashleigh M.; Rohleder, Cathrin; Ho, Nicholas; McHugh, Catherine; Jones, Graham; Song, Yun Ju Christine; Hickie, Ian B.; Scott, Elizabeth M.
Abstract: Aim: Young people with common mood disorders face the prospect of shortened life expectancy largely due to premature cardiovascular disease. Metabolic dysfunction is a risk factor for premature cardiovascular disease. There is an ongoing debate whether metabolic dysfunction can be simply explained by weight gain secondary to psychotropic medications or whether shared genetic vulnerability, intrinsic immune‐metabolic disturbances or other system perturbations (e.g. dysregulated sympathetic nervous system, circadian dysfunction) are more relevant determinants of premature cardiovascular disease. Thus, we aimed to investigate underlying drivers of metabolic dysfunction and premature cardiovascular disease in young people in the early phases of common mood disorders. Methods: We evaluated the relationships between insulin resistance (assessed by HOMA2‐IR) and body mass index (BMI), sex, diagnosis, medication, inflammatory markers and hormonal factors in 327 inpatients with emerging affective and major mood disorders admitted to the Young Adult Mental Health Unit, St Vincent's Private Hospital, Sydney. Results: While HOMA2‐IR scores were positively associated with BMI ( r s  = 0.465, p  < .001), they were also higher in those prescribed mood stabilizers ( p  = .044) but were not associated with specific diagnoses, other medication types or the number of prescribed medications. Further, high‐sensitivity C‐reactive protein levels (but not thyroid‐stimulating hormone and ferritin levels) were positively associated with HOMA2‐IR ( r s  = 0. 272, p  < .001) and BMI ( r s  = . 409, p  < .001). Conclusions: In addition to BMI, other non‐specific markers of inflammation are associated with early metabolic dysfunction in young people with emerging affective and major mood disorders.